Dried blood spot analysis for rat and dog studies: validation, hematocrit, toxicokinetics and incurred sample reanalysis. (April 2015) - Wickremsinhe, Enaksha
Background : Execution of experiments to introduce dried blood spot (DBS) sampling for preclinical GLP studies and subsequent clinical studies.Results : Bridging data showed high concordance with DBS:plasma ratios of 0.9 in rats and 1.1 in dogs, demonstrating no preferential uptake or association with cellular components of the blood. The DBS methodology was fully validated incorporating additional experiments pertinent to DBS sampling, storage and analysis. Individual hematocrit (Hct) values in the test animals (rats and dogs) were within the validated Hct range. DBS concentration data and the resulting TK profiles were not impacted by an Hct bias. Incurred sample reanalysis showed high correlation in dogs (97%) and rats (100%) meeting acceptance criteria.Conclusion : Successfully validated and adopted DBS for preclinical GLP studies.